Exaggerating, mislabeling or simulating obsessive-compulsive symptoms: Case reports of patients claiming to have obsessive-compulsive disorder - Fontenelle, Leonardo F.; Lins-Martins, Natalia M.; Melca, Isabela A.; Lima, Andre Luis C.; Menezes, Gabriela B. de; Torres, Albina Rodrigues [UNESP]; Yuecel, Murat; Miguel, Euripedes C.; Mendlowicz, Mauro V. (Elsevier B.V., 2014)
Background: There are no reported cases of factitious or simulated obsessive compulsive disorder (OCD). However, over the last years, our clinic has come across a number of individuals that seem to exaggerate, mislabel or even intentionally produce obsessive and/or compulsive symptoms in order to be diagnosed with OCD.Methods: In this study, experienced clinicians working on a university-based OCD clinic were requested to provide clinical vignettes of patients who, despite having a formal diagnosis of OCD, were felt to display non-genuine forms of this condition.Results: Ten non-consecutive patients with a self-proclaimed diagnosis of OCD were identified and described. Although patients were diagnosed with OCD according to various structured interviews, they exhibited diverse combinations of the following features: (i) overly technical and/or doctrinaire description of their symptoms, (ii) mounting irritability, as the interviewer attempts to unveil the underlying nature of these descriptions; (iii) marked shifts in symptom patterns and disease course; (iv) an affirmative yes pattern of response to interview questions; (v) multiple Axis I psychiatric disorders; (vi) cluster B features; (vii) an erratic pattern of treatment response; and (viii) excessive or contradictory drug-related side effects.Conclusions: In sum, reliance on overly structured assessments conducted by insufficiently trained or naive personnel may result in invalid OCD diagnoses, particularly those that leave no room for clinical judgment. (C) 2014 Elsevier Inc. All rights reserved.